2017
DOI: 10.1177/1461444817744790
|View full text |Cite
|
Sign up to set email alerts
|

Doing stigma: Online commenting around weight-related news media

Abstract: Weight stigma results from the mediatisation of 'obesity'; conceptually, a medicalised problem resulting from personal bodily irresponsibility. We undertake a frame analysis of 1452 comments on a thematically-related online news article published via The Guardian, about the status of 'obesity' as a disability in EU employment law. We identify three themes: weight as a lifestyle choice or disability; weight as an irresponsible choice, and weight as a simple or complex issue. We contend that the design of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
0
18
0
2
Order By: Relevance
“…Online discussions on health issues have received much research attention over the past few years (see Figure 2; n = 154). For example, researchers studied stigma and/or negativity in comments on weight-related news (Brooker et al, 2018), surgeons (Donnally et al, 2018), breastfeeding (Len-Rios, Bhandari and Medvedeva, 2014), on LGBT people confronted with hate speech (Baider, 2018), and tested whether one-sided UCs affect opinions and intentions about home birth (Witteman et al, 2016), as well as narrative formats and UCs’ role in preventive health measures (Stavrositu and Kim, 2015). Apart from the aforementioned research, studies were conducted on weight-loss apps (Frie et al, 2017), rape myths on Facebook (Clay, 2019), and online professional textual feedback’s value (Tang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online discussions on health issues have received much research attention over the past few years (see Figure 2; n = 154). For example, researchers studied stigma and/or negativity in comments on weight-related news (Brooker et al, 2018), surgeons (Donnally et al, 2018), breastfeeding (Len-Rios, Bhandari and Medvedeva, 2014), on LGBT people confronted with hate speech (Baider, 2018), and tested whether one-sided UCs affect opinions and intentions about home birth (Witteman et al, 2016), as well as narrative formats and UCs’ role in preventive health measures (Stavrositu and Kim, 2015). Apart from the aforementioned research, studies were conducted on weight-loss apps (Frie et al, 2017), rape myths on Facebook (Clay, 2019), and online professional textual feedback’s value (Tang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on online discourse or online trust focus on particular aspects, such as quality dimensions (Ziegele et al, 2018) or the trustworthiness of online discourses (Tustin et al, 2018). Studies on health care and lifestyle applied these questions on one concrete topic, such as malicious and stigmatizing comments on weight-related news (Brooker et al, 2018). In addition, research on discourse architecture reflected these aspects mostly from a technical perspective such as the flagging of uncivil comments in comment sections (Naab et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that media reporting concerning obesity is poorer quality and involves stigmatising discourse (1) . The microblogging social media platform, Twitter, has 321 million users sharing information globally and is therefore of particular research interest.…”
mentioning
confidence: 99%
“…While it has not been the aims of our analysis, all of this has potential implication for the study of forum architecture, which has been issues of substantial concern in the field of journalism (Knustad, 2018). Brooker et al's (2017) Frame Analysis of forums from The Guardian led them conclude that the architecture itself aided the production of polarized positions and "discourages users from developing alternative terminologies for producing counter-narratives" (ibid. : 3201).…”
Section: Discussionmentioning
confidence: 99%